2011
DOI: 10.1177/1090820x11418202
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix in the Management of the Burn Patient

Abstract: Although the principles of burn management are still primarily focused on survival, as advances are realized in resuscitation, nutrition, and wound management, the functional and aesthetic outcomes following burn injury have become increasingly important. Acellular dermal matrix materials, which allow surgeons to minimize skin graft donor site morbidity in the process of repairing injured areas, play a role in addressing these important issues. Many favorable reports have been published, but they are generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 53 publications
(73 reference statements)
0
39
0
Order By: Relevance
“…Reconstructive methods of postburn scar contractures include skin grafts, local advancement flaps (Z-plasty, K-plasty, or their combination), distant flaps, and free flaps [8]. STSG remains the standard treatment of deep-dermal and full-thickness burns; however, the delivered dermis is sometimes insufficient to prevent functional and cosmetic disability [9]. Many studies have reported that artificial dermal substitutes improve the quality of skin grafts [10], that the amount of the dermal component contributes to the prevention of contractures [11], and that the application of a dermal substitute such as AlloDerm or Matriderm is an effective option in reconstruction [12].…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructive methods of postburn scar contractures include skin grafts, local advancement flaps (Z-plasty, K-plasty, or their combination), distant flaps, and free flaps [8]. STSG remains the standard treatment of deep-dermal and full-thickness burns; however, the delivered dermis is sometimes insufficient to prevent functional and cosmetic disability [9]. Many studies have reported that artificial dermal substitutes improve the quality of skin grafts [10], that the amount of the dermal component contributes to the prevention of contractures [11], and that the application of a dermal substitute such as AlloDerm or Matriderm is an effective option in reconstruction [12].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] However, because it only functionally serves to replace the dermal layer, epidermal coverage in the form of a split-thickness skin graft is still needed. Regardless, numerous studies have demonstrated that the addition of acellular dermal matrix use in this setting results in a faster healing time, 9,10 better aesthetic outcome with improved skin elasticity, and reduced scar contracture [11][12][13][14][15][16][17][18][19] ; can serve as a temporizing measure to avert the need for emergency surgery 19 ; and allows improved mobility and function of joints that require skin coverage.…”
Section: Basic Sciencementioning
confidence: 99%
“…Multiple new cellular processes and molecules have been introduced in recent times to treat burn injuries [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Experimental studies in molecular biology and transgenic animal models created a scope of further exponential improvement [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides some general treatments like massage and use of moisturizing agents, pressure garments, silicone sheeting, topical as well as intralesional steroids, and experimental therapies such as interferon, skin grafting and different types of flaps are used for the reconstruction of contractures. Thus autograft, human allograft, fresh, frozen and glycerolized porcine xenograft, in vitro cultured keratinocytes, dermal regenerated template ( biological raw materials), dermal analogue of bovine collagen covalently linked to chondroitin-5-sulphate, epidermal analogue of silicon, biodegradable collagen dermal analogue, adipose tissue, fetal cells, embryonic stem cells, platelets, placental and amniotic fluid cells, stem cells, nanoparticles are only a few examples which are used in burn wound management [1][2][3][4][5][6][7][8][9][10][11][12][13][14].Againdyspigmentation particularly hypopigmentation in the scars is a common phenomenon due to disturbance of melanogenesis [18]. This may lead to social humiliation and sometimes isolation of the affected person [19][20][21].…”
Section: Introductionmentioning
confidence: 99%